Penyelarasan gangguan antara sel dalam komunikasi tanpa wayar - Mohd Kasim, Noor Shahida (Penerbit UTeM Press, 2024)
The introduction of wireless communication technology brought great changes in our lives. Although there are limiting factors, techniques such as NetMIMO and DFFR help reduce interference between cells. The combination of these two techniques improves performance in LTE-A communication systems. The book is divided into five chapters that include introduction, theory of LTE-A and NetMIMO, background of interference coordination between cells, as well as system implementation analysis. Power allocation algorithms such as WF, IWF, and LC-IWF are developed to improve the system. This book provides detailed information on the development of wireless communication from theory to implementation, as part of the author's PhD thesis. The author hopes that the reader will benefit from the contents of this book.